Model Building And Forecasting Of Climate Data For Tourism Area In Bangladesh - Hossen, Sayed Mohibul (2022)
Climatic variables such as temperature, rainfall, and humidity affect the choice of destination and the distribution pattern of tourists in different seasons. So, the main objective of this research is to modelling and forecasting the climatic variable of different tourist spots. More specifically, to examine the impact of seasonality on tourist’s arrival and income from tourism that contributes to the national economy of Bangladesh. Wherein, the effect of these climatic variables was assessed using the SANCOVA modelling framework modified by the ANCOVA model, to explain the current contribution of climate change on GDP. SARIMA model was applied for modelling at seven attractive sightseeing diverse places in Bangladesh and forecast up to the year 2050. From the analysis, we have found that the maximum and minimum temperature is slightly increasing at approximately 10C but decreasing approximately 20C. In July, rainfall amounts to 800 mm (31.5 in) in Sylhet, to 750 mm (29.5 in) in Chittagong, to 900 mm (35.5 in) in Cox's Bazar. Visitors belonging to low humidity countries can travel to Bangladesh in the rainy season, and from high humidity countries can discover all year-round. In the analysis, we found that seasonality has 91% effect on tourist’s arrival in Bangladesh and recommends that, if tourist’s arrival will increase thousand per season, then income will increase on average by 0.527 million Taka per season. Also, if expenditure for tourism development will increase 0.1 million Taka per year, then income will increase 0.181 million Taka every season.